Gender Differences in Job Search and the Earnings Gap: Evidence from Business Majors - Patricia Cortes; Jessica Pan; Laura Pilossoph; Basit Zafar (Institute of Labor Economics (IZA), 2021)
To understand gender differences in the job search process, we collect rich information on job offers and acceptances from past and current undergraduates of Boston University's Questrom School of Business. We document two novel empirical facts: (1) there is a clear gender difference in the timing of job offer acceptance, with women accepting jobs substantially earlier than men, and (2) the gender earnings gap in accepted offers narrows in favor of women over the course of the job search period. Using survey data on risk preferences and beliefs about expected future earnings, we present empirical evidence that the patterns in job search can be partly explained by the higher levels of risk aversion displayed by women and the higher levels of overoptimism (and slower belief updating) displayed by men. We develop a job search model that incorporates these gender differences in risk aversion and (over)optimism about prospective offers. Our counterfactual exercises show that simple policies such as eliminating "exploding offers" by allowing students to hold onto offers for an additional month, or providing them with accurate information about the labor market, can reduce the gender gap significantly.
Keywords: D83; D91; J64; 330; gender; job search behavior; risk aversion; overconfidence